2016
DOI: 10.1002/ajh.24224
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary platelet thrombi and vascular pathology in acute chest syndrome in patients with sickle cell disease

Abstract: A growing body of evidence suggests a role for platelets in sickle cell disease (SCD). Despite the pro-inflammatory, occlusive nature of platelets, a role for platelets in acute chest syndrome (ACS), however, remains understudied. To provide evidence and potentially describe contributory factors for a putative link between ACS and platelets, we performed an autopsy study of 20 SCD cases – 10 of whom died from ACS and 10 whose deaths were not ACS-related. Pulmonary histopathology and case history were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
7
32
0
Order By: Relevance
“…Our finding that pulmonary vaso-occlusion occurs in precapillary pulmonary arterioles is distinct from the current paradigm for systemic vaso-occlusion, which suggests that postcapillary venules are the principal site of vaso-occlusion (1). These new observations of arteriolar pulmonary vaso-occlusion are supported by recent clinical studies that reveal selective occlusion of pulmonary artery branches and arterioles by aggregates of platelets in lung autopsies (27) and CT scans (32) of SCD patients diagnosed with lung injury.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our finding that pulmonary vaso-occlusion occurs in precapillary pulmonary arterioles is distinct from the current paradigm for systemic vaso-occlusion, which suggests that postcapillary venules are the principal site of vaso-occlusion (1). These new observations of arteriolar pulmonary vaso-occlusion are supported by recent clinical studies that reveal selective occlusion of pulmonary artery branches and arterioles by aggregates of platelets in lung autopsies (27) and CT scans (32) of SCD patients diagnosed with lung injury.…”
Section: Discussionsupporting
confidence: 62%
“…The current treatment for acute chest syndrome is primarily supportive, and the molecular mechanism remains largely unknown. In a recent autopsy study (27), pulmonary histopathology of acute chest syndrome patients revealed occlusion of the pulmonary vasculature with aggregates of platelets or erythrocytes, suggesting that the molecular events surrounding pulmonary vaso-occlusion contribute to lung injury. Our data suggest that systemic vaso-occlusive crisis also produces pulmonary vaso-occlusion by platelet-neutrophil aggregates that arrest blood flow in the pulmonary arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many haemostatic alterations leading to a hypercoagulable state in SCD patients, platelet activation is commonly observed during acute vaso‐occlusive episodes (Tomer et al , ), and might mediate the genesis of pulmonary platelet thrombi during ACS (Anea et al , ). The higher platelet count found in our study at the diagnosis of ACS with PAT argues for a contributing role of platelets in pulmonary thrombogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous descriptions on the lung pathology of SCD are scarce, and all are autopsy based. In these studies, the frequency of lung involvement is high (Adedeji et al , ; Haque et al , ; Graham et al , ; Anea et al , ). To our knowledge this is the first paper to describe arterial, venous and alveolar wall alterations in SCD lungs, with the novel description of venous thickening and focal PCH in SCD, in the largest autopsy series so far.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of the vascular lesions in SCD has been described in a few autopsy studies (Adedeji et al , ; Haque et al , ; Graham et al , ; Anea et al , ). Pulmonary vascular changes were frequent findings and included recent or recanalised thrombus and occlusive arterial lesions, such as medial layer hypertrophy with or without intimal proliferative lesions.…”
mentioning
confidence: 99%